Novel small molecule retrograde transport blocker confers post-exposure protection against ricin intoxication - Xu Zhao; Haixia Li; Jia Li; Kunlu Liu; Bo Wang; Yuxia Wang; Xingzhou Li; Wu Zhong (Elsevier, 2020)
Ricin is a highly toxic type 2 ribosome-inactivating protein (RIP) which is extracted from the seeds of castor beans. Ricin is considered a potential bioterror agent and no effective antidote for ricin exists so far. In this study, by structural modification of a retrograde transport blocker Retro-2cycl, a series of novel compounds were obtained. The primary screen revealed that compound 27 has an improved anti-ricin activity compare to positive control. In vitro pre-exposure evaluation in Madin-Darby Canine Kidney (MDCK) cells demonstrated that 27 is a powerful anti-ricin compound with an EC50 of 41.05 nmol/L against one LC (lethal concentration, 5.56 ng/mL) of ricin. Further studies surprisingly indicated that 27 confers post-exposure activity against ricin intoxication. An in vivo study showed that 1 h post-exposure administration of 27 can improve the survival rate as well as delay the death of ricin-intoxicated mice. A drug combination of 27 with monoclonal antibody mAb4C13 rescued mice from one LD (lethal dose) ricin challenge and the survival rate of tested animals is 100%. These results represent, for the first time, indication that small molecule retrograde transport blocker confers both in vitro and in vivo post-exposure protection against ricin and therefore provides a promising candidate for the development of anti-ricin medicines. Key words: Ricin toxin, Ribosome-inactivating proteins, Retrograde transport, Post-exposure antidote, Ricin antibody